Analysis of the Implementation of the STEAM Approach in Entrepreneurship Learning To Support Planning for the Implementation of Entrepreneurship Curriculum in Elementary Schools - Widia Indra Kartika; Rokhmaniyah Rokhmaniyah (Universitas Sebelas Maret, 2019)
The purpose of this study is to analyze: 1) the implementation of the STEAM approach in class IV entrepreneurship learning activities in Waluyo Kebumen State Elementary School 2, and 2) evaluation of the fourth grade entrepreneurship learning activities in Waluyo Kebumen State Elementary School 2. This research uses descriptive analytical method with a qualitative approach. Data collection techniques carried out by observation, interview, and study documentation. The results of the study include: 1) entrepreneurial learning activities with the STEAM approach in grade IV at State Elementary School 2 Waluyo Kebumen appropriate to achieve learning objectives and can foster student entrepreneurial spirit, and 2) the evaluation of entrepreneurship learning activities in class IV at Waluyo Kebumen 2 Elementary School was conducted through written tests, process assessments, and results in making products from beads and woven pandanus leaves.